Anxiety and stress among healthcare professionals during COVID-19 in Ethiopia: systematic review and meta-analysis. Issue 2 (7th February 2023) - Hasen, Aragaw Asfaw; Seid, Abubeker Alebachew; Mohammed, Ahmed Adem
Abstract : Objective: This study intended to assess the impact of COVID-19 pandemic on anxiety and stress among healthcare professionals in Ethiopia. Design: This study applied a design of systematic review and meta-analysis of observational studies. Data sources: Eligibility criteria and outcomes: Observational studies examining anxiety and stress among healthcare professionals in Ethiopia following COVID-19 pandemic were considered. The primary outcomes were the prevalence of anxiety and stress and the secondary outcomes were factors associated to the prevalence of anxiety and stress. Data extraction and synthesis: Two authors extracted the data and performed quality assessment independently. The Newcastle-Ottawa Scale was used to evaluate the quality of eligible studies. Random-effect model with the inverse variance method was used to estimate the pooled effect size of the outcome variables with its 95% CI. Publication bias was checked by DOI plot and Luis Furuya Kanamori index. Stata V.14.0 (StataCorp) software was used for statistical analysis. Results: Thirteen studies were included. From eight studies the pooled prevalence of anxiety was 46% (95% CI 0.30% to 0.61%, τ 2 =0.0497, I 2 =99.07%, p<0.001). Nine studies reported about stress and the pooled prevalence was 51% (95% CI 0.41% to 0.62%, τ 2 =0.0253, I 2 =97.85%, p<0.001)). Age, sex, marital status, working department, history of contact with confirmed COVID-19 cases and profession were associated factors for high level of anxiety and stress. Conclusions: COVID-19 pandemic highly affects mental health of healthcare professionals in Ethiopia. Anxiety and stress were among reported mental health problems among healthcare professionals during the pandemic. Timely psychological counselling programmes should be applied for healthcare professionals to improve the general mental health problems. PROSPERO registration number: CRD42022314865.